Aktivitas Antiinflamasi dan Analgesik dari Kombinasi Ekstrak Daun Carica papaya dan Ocimum sanctum - Eem Masaenah; Sofyan Ramani; Fredy Arifta Nasel; Zuliar Permana; Jenika Ariyani; Rihadatul Ayis Rahma; Rega Juwanda (Pengurus Pusat Ikatan Apoteker Indonesia, 2026)
Inflammation and inflammatory pain remain important clinical problems, and long-term use of anti-inflammatory or analgesic drugs is often associated with adverse effects. Papaya (Carica papaya) and basil (Ocimum sanctum) leaves are widely used in traditional Indonesian medicine, yet evidence regarding their combined use remains limited. This study evaluated the phytochemical profile, anti-inflammatory activity, and analgesic effects of ethanolic extracts prepared from papaya leaf simplicia (EP), basil leaf simplicia (EK), and combined simplicia extracts at ratios of 1:1 (EP1K1), 3:1 (EP3K1), and 1:3 (EP1K3). Phytochemical screening revealed the presence of flavonoids, phenolics, alkaloids, saponins, and triterpenoids in all extracts, while tannins were detected only in basil extract. In vitro evaluation using the bovine serum albumin (BSA) protein denaturation assay showed that basil extract exhibited the strongest activity (IC₅₀ = 82.44 μg/mL), whereas the combined extracts predominantly exhibited additive effects. In vivo testing using the carrageenan-induced paw edema model showed that papaya extract produced the highest anti-inflammatory inhibition (64.41%), while basil extract showed comparable activity to diclofenac sodium. Analgesic evaluation using the acetic acid-induced writhing test indicated that the basil-rich combination (EP₁K₃) showed the highest analgesic protection among the tested combinations. These findings indicate that papaya and basil extracts exhibit distinct yet complementary anti-inflammatory and analgesic activities. The combined simplicia extracts demonstrated additive pharmacological effects support the traditional use of these plants for the development of standardized herbal preparations.